Violent Speech Acts in the South A and B areas of José Martí District - Massiel Hernández-González; Irina Bidot-Martínez; Mercedes Causse-Cathcart (Maestro y Sociedad, 2018)
A new tendency in speakers to prefer nonpolite strategies can also include some rude speech acts and to get the control of the other person All these are the reasons that lead the autor of this paper to start this research that consist of an study case of the courtesy emphazizing in the verbal violence, taking also into account not only the spanish speech but the recent studies made in Cuba. The South A and B of Santiago community of José Martí District is an example of that and for that reason it became of special interest for the analysis of those violent samples in the use of the language. The objective of the paper is to describe the linguistic elements that characterized the violent speech acts in that neighbourhood with the aim to contribute to the sociocultural characterization of the community so a multidisciplinary intervention can be developed there. Uncovered recorders the work with the field study notebook and the application of a social habit tests were the techniques used. All the results obtained were triangled.